A quality of system routing based on neighborhood interference detection and mitigation in wireless sensor network - Ling Zhang; Ziyun Ni (International Journal of Distributed Sensor Networks)
The current quality of system routing available in wireless sensor network mainly provides assurance for traffic flow, with little consideration on full use of network resource, like bandwidth. Aiming at solving these problems, this article proposes a quality of system routing method based on neighborhood interference detection and mitigation. First, the algorithm uses a sink node as root node to establish a minimum spanning tree for the network to obtain the depth of each node. Then, each node dynamically updates its interference degree by contiguous iterations during neighboring nodes communication. Finally, the interference degree, packet level, residual energy, and node depth are combined to establish a multipath route to enhance the network bandwidth and thus improve the quality of system. Experimental results show that the algorithm can not only effectively balance the network load but also reduce the network packet delay and improve the network throughput. It also has a good network lifetime; thus, it can effectively improve the quality of system of wireless sensor network.